Exosomal MiRNAs in Osteosarcoma: Biogenesis and Biological Functions - Tang, Jinxin; He, Jieyu; Feng, Chengyao; Tu, Chao (Frontiers in Pharmacology, 2022)
MiRNAs are a group of non-coding RNA molecules that function in mRNA translational inhibition via base-pairing with complementary sequences in target mRNA. In oncology, miRNAs have raised great attention due to their aberrant expression and pivotal roles in the pathogenesis of multiple malignancies including osteosarcoma. MiRNAs can be transported by exosome, the nano-extracellular vesicle with a diameter of 30 to 150 nm. Recently, a growing number of studies have demonstrated that exosomal miRNAs play a critical role in tumor initiation and progression, by exerting multiple biological functions including metastasis, angiogenesis, drug resistance and immunosuppression. In this review, we aim to depict the biogenesis of exosomal miRNAs and summarize the potential diagnostic and therapeutic functions of exosomal miRNAs in osteosarcoma.